1991
DOI: 10.3109/01421599109036755
|View full text |Cite
|
Sign up to set email alerts
|

Student contact with patients in hospital: frequency, duration and effects

Abstract: Student-patient contacts on the wards were monitored by having students keep daily logs of patient contacts during a 5-week period of routine clinical attachments in a teaching hospital. After being discharged patients were followed up by postal questionnaire. Results indicated that on average students spend substantially less time with patients than is allowed for in the curriculum. Variability in contact time was high both within and between attachments to different wards. Patient satisfaction with student c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…Students did not make full use of the learning opportunities provided in either setting. Student attendance figures are low in this study and McKergow et al . (1991) have already shown that students spends less contact time with patients than is allowed for in the curriculum.…”
Section: Discussioncontrasting
confidence: 78%
“…Students did not make full use of the learning opportunities provided in either setting. Student attendance figures are low in this study and McKergow et al . (1991) have already shown that students spends less contact time with patients than is allowed for in the curriculum.…”
Section: Discussioncontrasting
confidence: 78%
“…· Considerable time is spent on activities with little educational value (Cook et al, 1992;Schamroth & Haines, 1992). · Individual students differ substantially with regard to the activities they perform (Friedman et al, 1978;McKerwgow et al, 1991;Cook et al, 1992;Tortolani et al, 1997). · Students have educational contacts mainly with house officers and registrars and fellow students and to a lesser degree with senior staff (Remmen et al, 1998).…”
Section: Research ® Ndings On Clerkshipsmentioning
confidence: 97%
“…Very few studies have investigated the frequency with which students are able to undertake different procedures during medical training, 12,28 or have investigated the duration of student contact with patients in different rotations. 29 In addition, the number of patient assessments does not give an indication of the quality of the interaction. Evidence of the decline in time devoted to clinical encounters 13 suggests a measure of both the number of patient assessments and the duration or quality of the encounter might be warranted.…”
Section: Further Researchmentioning
confidence: 99%